A note on arbitrage under transaction costs - Albrecht Irle; Claas Prelle (Kiel Institute for the World Economy (IfW), 2008)
Guasoni (2006) introduced a simple condition for the absence of arbitrage opportunities. In this note we show that his results remain valid under a weaker notion of arbitrage which arises by excluding liquidation costs from the value process of a portfolio.
Keywords: G10; G12; C60; 330; Arbitrage; transaction costs; fractional Brownian motion; Wertpapierhandel; Arbitragegeschäft; Transaktionskosten; Markovscher Prozess; Theorie